2021
DOI: 10.6007/ijarbss/v11-i12/11799
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Knowledge, Financial Socialization, Financial Behaviour, and Financial Strain on Young Adults’ Financial Well-Being

Abstract: Financial well-being refers to one's overall satisfaction with their current financial condition, and it plays a significant part in young adults' overall success as well as their ability to overcome psychological health concerns. It has become a crucial concern for individuals, households, societies, and countries in recent years, yet research on the subject is sparse and dispersed among fields. As a result, the current research assessed an empirical financial wellbeing model based on Malaysian young adults' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
2
17
0
3
Order By: Relevance
“…FS was negatively related to SFWB, confirming the past literature (Boss, 2001; Delafrooz and Paim, 2011; Mahdzan et al ., 2019; Sabri et al ., 2021). This means that those who face economic hardships and feel depressed thinking about their finances would be less confident and less satisfied with his or her financial situation.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…FS was negatively related to SFWB, confirming the past literature (Boss, 2001; Delafrooz and Paim, 2011; Mahdzan et al ., 2019; Sabri et al ., 2021). This means that those who face economic hardships and feel depressed thinking about their finances would be less confident and less satisfied with his or her financial situation.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Past studies have found that FS relates negatively to FWB (e.g. Boss, 2001;Delafrooz and Paim, 2011;Mahdzan et al, 2019;Sabri et al, 2021). Hence, the second hypothesis to be tested is as follows:…”
Section: Financial Stressmentioning
confidence: 97%
“…Demographic and socioeconomic characteristics, for example, age, ethnicity, gender, education, income, and marital status are the most frequently known factors (Hira & Mugenda, 1999). In addition to the demographics, other factors are also revealed as influential determinants of financial health for the context of Malaysia, for example, money attitude financial practices, emotion coping, and self-efficacy (Sabri et al, 2020a), financial behaviour, financial strain, financial socialization, and financial knowledge (Sabri et al, 2021a), financial capability, and financial literacy (Sabri & Zakaria, 2015), debt management (Abdullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Masyarakat yang tinggal pada daerah perkotaan cenderung memiliki akses terhadap pendidikan yang baik sehingga memiliki pengetahuan tentang pengelolaan keuangan yang baik. Hal ini senada dengan Sabri et al, (2021) yang mengatakan bahwa urban community cenderung memiliki financial management knowledge yang baik jika dibandingkan dengan rural community. Namun, hal ini tidak sejalan dengan pepatah lama yang berkembang dalam masyarakat, dimana masyarakat memiliki kepercayaan bahwa rural community meskipun tidak memiliki financial management knowledge yang baik, namun mereka memiliki personal financial management behavior yang lebih baik daripada urban community.…”
Section: Abstrakunclassified
“…Beberapa penelitian terdahulu telah menunjukkan hasil bahwa financial knowledge merupakan salah satu faktor penentu financial management behavior seseorang (A. Robb & S. Woodyard, 2011;Pathirannahalage & Abeyrathna, 2020;Rai et al, 2019;Sabri et al, 2021). Seseorang yang memiliki financial management knowledge yang baik cenderung juga memiliki financial management behavior yang baik pula.…”
Section: Hasil Dan Pembahasanunclassified